2014
DOI: 10.1371/journal.pone.0087543
|View full text |Cite
|
Sign up to set email alerts
|

After-Ripening Induced Transcriptional Changes of Hormonal Genes in Wheat Seeds: The Cases of Brassinosteroids, Ethylene, Cytokinin and Salicylic Acid

Abstract: Maintenance and release of seed dormancy is regulated by plant hormones; their levels and seed sensitivity being the critical factors. This study reports transcriptional regulation of brassinosteroids (BR), ethylene (ET), cytokinin (CK) and salicylic acid (SA) related wheat genes by after-ripening, a period of dry storage that decays dormancy. Changes in the expression of hormonal genes due to seed after-ripening did not occur in the anhydrobiotic state but rather in the hydrated state. After-ripening induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 62 publications
0
42
0
1
Order By: Relevance
“…Previous studies have described the significance of plant hormones in metabolic and signaling aspects and their probable role in the maintenance and release of dormancy in seeds of cereal crops [43,119,120]. Among plant growth hormones, abscisic acid (ABA) and gibberellin (GA) play important roles in regulation of dormancy and germination, ABA induces dormancy and GA stimulates seed germination [121,122].…”
Section: Plant Growth Hormonesmentioning
confidence: 99%
“…Previous studies have described the significance of plant hormones in metabolic and signaling aspects and their probable role in the maintenance and release of dormancy in seeds of cereal crops [43,119,120]. Among plant growth hormones, abscisic acid (ABA) and gibberellin (GA) play important roles in regulation of dormancy and germination, ABA induces dormancy and GA stimulates seed germination [121,122].…”
Section: Plant Growth Hormonesmentioning
confidence: 99%
“…It was shown that some genes associated with storage mobilization, cell wall modification were highly expressed in after-ripened seeds to dormant seeds of Arabidopsis and wheat [45,46]. Although transcriptional profiles and molecular mechanism underlying dormancy release by AR are conserved between species, there are their own unique regulatory mechanisms in different species [46,48]. In this study, seeds of LH14 display the obvious AR period during dry storage despite easily losing their dormancy.…”
Section: Discussionmentioning
confidence: 73%
“…In O. sativa the cytokinin oxidase/dehydrogenase4 integrates the interaction between cytokinin and auxin signaling to control the crown root formation (Gao et al, 2014a). Response regulators (RRs) have been also characterized in O. sativa and T. aestivum (Chitnis et al, 2014).…”
Section: Cytokinin Response Regulatorsmentioning
confidence: 99%